Essential Oils Enriched Self-nano-emulsifying Systems for Effective Oral Delivery of Zaleplon for Improvement of Insomnia Treatment - El-Enin, Hadel A. Abo; Khalifa, Amany Salah (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Insomnia is usually associated with mental and physical daytime impairment. Zaleplon (Zp) is indicated in insomnia management but its limited aqueous solubility led to its low bioavailability (BAV) ~30%. Self-nanoemulsifying drug delivery system (SNEDDS) was a recommended nano-delivery system for improvement poorly soluble drugs’ oral bioavailability. Consequently, this study aimed to prepare SNEDDS entrapped Zp using essential oils (EOs) have insomnia management effect. Materials and Methods: Different EOs, surfactants and co-surfactants in varying ratios were used in preparing Zp-loaded SNEDDS, which were chosen according to their ability to ease the emulsification and improve Zp solubility. To optimize the formulations; Zp-SNEEDS formulae were characterized for particle-size, zeta-potential, emulsification-time, and drug loading capacity. Additionally, in-vitro release and stability studies were performed to provide a perception on the stability and enhancing Zp release from Zp-SNEDDS formulae. To improve Zp-SNEDDS activity; BAV study and psychomotor evaluation test were carried out in albino mice. Results: The selected optimized formulae containing Tween80, PEG400 and anise oil had nanoparticle size (~98nm), loading capacity up to 40%, emulsification time~34sec and increased Zp dissolution rate up to 2 folds compared to pure Zp suspension. Zp-SNEEDS’ BAV is 1.29 and increases in the sleep time up to 165min which equal to the synergetic effect of anise oil and zaleplon alone. Conclusion: The significant increase in the rate and extent of Zp oral absorption from nano-positively charge Zp-SNEEDS with high BAV and increases in sleeping time indicates the effectiveness of Zp-SNEEDS in improving Zp oral absorption and therapeutic effect in insomnia treatment.
Keywords: Nanoparticles; Zaleplon; Essential oils; Insomnia; SNEDDS